MOTIVASI SISWA KELAS XI DALAM MENGIKUTI PEMBELAJARAN PENJASORKES DI SMA NEGERI 5 PINGGIR SEBANGA-DURI TAHUN AJARAN 2022/2023 - Jaya, Ade Nopian; Juita, Ardiah; Hidayat, Hirja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The aim of this research is to investigate the motivation of class This type of research is quantitative descriptive research. The population in this study were 195 class The sampling technique in this study was a random sampling technique of 25% of the total population, so the sample in this study was 49 people. The research instrument used was a Likert scale. Based on the research results, the conclusion obtained in this research is: This type of research is quantitative descriptive research. The population in this study were 195 class The sampling technique in this study was a random sampling technique of 25% of the total population, so the sample in this study was 49 people. The research instrument used was a Likert scale. Based on the research results. with an average motivation questionnaire score of 67.68%, which is classified as moderate. Keywords: Student Motivation in participating in Physical Education Learning